2004
DOI: 10.7863/jum.2004.23.9.1141
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sonographically Guided Fine-Needle Aspiration Yield in Submucosal Tumors of the Gastrointestinal Tract

Abstract: Objective. To study the yield of endoscopic ultrasonographically guided fine-needle aspiration cytologic examination in the diagnosis of submucosal masses. Methods. From 1999 to 2003, 10 patients underwent ultrasonographically guided fine-needle aspiration for the cytologic diagnosis of submucosal masses in our institution. The endoscopic ultrasonography records and the cytology database were consulted, and the reports were analyzed, as were slide material and the technical aspects related to these procedures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 23 publications
1
27
1
Order By: Relevance
“…Because endoscopic biopsy may not be revealing as a result of the submucosal nature of the tumor, EUS has recently evolved as a vital diagnostic modality for GISTs [11]. The ability to perform EUS fine-needle aspiration has been associated with a diagnostic accuracy of 80%-85% [12,13]. Percutaneous biopsy should rarely be used because it is associated with a significant risk for tumor rupture, dissemination, and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Because endoscopic biopsy may not be revealing as a result of the submucosal nature of the tumor, EUS has recently evolved as a vital diagnostic modality for GISTs [11]. The ability to perform EUS fine-needle aspiration has been associated with a diagnostic accuracy of 80%-85% [12,13]. Percutaneous biopsy should rarely be used because it is associated with a significant risk for tumor rupture, dissemination, and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that EUS-FNA was diagnostic in 21 of 24 lesions that were negative on both brush cytology and mucosal forceps biopsy. This study and others concluded that EUS-FNA should be the diagnostic procedure of choice when standard methods, such as endoscopic mucosal forceps biopsy, fail to provide a definitive diagnosis (16)(17)(18)(19).…”
Section: Original Articlementioning
confidence: 65%
“…Those authors found that EUS-FNA had a sensitivity of 89% in the diagnosis of gastrointestinal lesions. Additionally, in a smaller series of 10 cases, Arantes et al 11 found that EUS-FNA had a sensitivity of 80% for submucosal tumors of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%